Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pengguna Jasa Ojek Online Di Solo - Ismail Hakim Asy Syidiq (Universitas Duta Bangsa Surakarta, 2021)
Online motorcycle taxi in solo is indeed very useful and very helpful for people who need an ease. The problem in this study is “What is the effect of service quality and price strategy on the satisfaction of users on online motorcycle taxi service in Solo”. The research method use was associative with a likert scale 1-5 using 20 questions in the form of a questionaire distributed to 40 solo residents. This study aims to determine how much influence the quality of service and strategy on online motorcycle taxi user satisfaction. It can be concluded that the service quality and pricing strategy has a great influence on the satisfaction of online motorcycle taxi users in Solo.